Olfactory Responses of Lariophagus distinguendus (Hymenoptera Pteromalidae) to Volatile Signals Derived from Host Habitats - Tang, Qingfeng (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2009)
The responses of female Lariophagus distinguendus (Hymenoptera: Pteromalidae) to volatile signals derived from its host habitats were investigated in a static four-chamber olfactometer. Our results demonstrated that the L. distinguendus females, regardless of experience, were apparently attracted by the odors released from the feces of Sitophilus zeamais adult that have never been applied in previous researches. Moreover, we compared the responses of female parasitoids to odors released from grains of wheat (Triticum aestivum Linn.) damaged by S. zeamais larvae, S. zeamais males, S. zeamais females and grains that were damaged mechanically. Results showed that artificially-damaged grains did not emit large amounts of volatiles that attracted the experienced parasitoid females emitted by grains damaged by S. zeamais larvae or females. Further experiments revealed that the experienced L. distinguendus females were strongly attracted to the wheat grains which had been infused with extract from the heads and thoraxes of weevil larvae or adult females compared with the wheat grains which had been infused with sodium phosphate. Eavesdropping on the sex pheromone signals emitted to attract mates allowed many predators and parasitoids to find and attack their host. The S. zeamais aggregation pheromones are also useful signals for experienced L. distinguendus females because their hosts, the larvae of the maize weevil S. zeamais, frequently exist in nearby grains. The effect of experience on the response of the parasitoids to several stimuli is also discussed.